2020
DOI: 10.1007/s11205-020-02428-2
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Effects of Parental Divorce and Parental Temporary Separation on Children’s Cognitive Abilities and Psychological Well-being According to Parental Relationship Quality

Abstract: We explore the effects of parental divorce and parental temporary separation on wellbeing of children at a specific stage of their development according to the parental relationship quality. Despite the importance of this subject, among previous studies only few consider very young children and are based on statistical methods properly tailored to enhance causal evaluations. We attempt to establish the effects on both cognitive abilities and psychological dimensions of children at age five by using data drawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 64 publications
0
19
1
5
Order By: Relevance
“…Firstly, control variables were set from individual- and family-level according to the characteristics of questionnaires to examine effects of discrepancies between parents’ educational aspirations and children’s educational expectations on LBC’s mental health level. However, the mental health of left-behind children in rural areas is also affected by many other factors, such as parents’ divorce or death [ 50 ], school climate [ 12 , 51 ], network addiction [ 52 ], peers’ effects [ 53 ], etc. Future researches should take these variables into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, control variables were set from individual- and family-level according to the characteristics of questionnaires to examine effects of discrepancies between parents’ educational aspirations and children’s educational expectations on LBC’s mental health level. However, the mental health of left-behind children in rural areas is also affected by many other factors, such as parents’ divorce or death [ 50 ], school climate [ 12 , 51 ], network addiction [ 52 ], peers’ effects [ 53 ], etc. Future researches should take these variables into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…They argue that for children whose parents are unlikely to break up, divorce is an unexpected shock, whereas children in high-risk marriages may well anticipate parental divorce and have grown accustomed to adversities in their lives through already high levels of family instability and conflicts even before the divorce. Likewise, using data drawn from the first three waves of the UK Millennium Cohort Study, Garriga and Pennoni ( 2020 ) also found that parental divorce appears to exert the most harmful effects among children whose parents enjoyed a very good parental relationship quality prior to separation.…”
Section: Predivorce Interparental Conflicts and Children’s Initial Re...mentioning
confidence: 96%
“… Some additional mixed (yet interesting) findings await to be more systematically clarified. For example, although a number of studies conducted in different decades have yielded evidence supporting that children in high-conflict marriages appeared to benefit from parental divorce (e.g., Amato et al, 1995 ; Booth & Amato, 2001 ; Brand et al, 2019 ; Garriga & Pennoni, 2020 ; Strohschein, 2005 ), some exceptional results do exist in a handful of studies indicating that when parental separation occurs in families with low levels of interparental conflicts, parental separation does not predict (the increases in) child adaptation problems (e.g., Xerxa et al, 2020 ). Such inconsistencies highlight the intriguing necessity of testing moderating factors and the possibility of curvilinear associations (e.g., a threshold level of predivorce interparental conflict in shaping developmental consequences of parental divorce).…”
Section: Key Limitations Of Prior Literature Directions For Future Re...mentioning
confidence: 99%
“…Misal, kondisi psikologis korban yang tidak bersalah yakni anak. Anak yang menyaksikan perceraian orangtua cenderung mengalami masalah perilaku dan hiperaktif (Garriga & Pennoni, 2020 serta kesulitan menyesuaikan diri dan khawatir apabila dihadapkan pada pernikahan kembali ayah serta ibu mereka dengan pasangan barunya masing-masing (Siegelman & Rider, 2018). Selain anak, yang juga dipertimbangkan ialah aspirasi dan harapan keluarga besar serta masyarakat terdekat yang menjadi mikrosistem serta mesosistemnya (Brofenbrenner dalam Santrock, 2018).…”
Section: Pendahuluanunclassified
“…Penelitian ini mengidentifikasi tiga pertimbangan, yaitu keengganan pasangan (suami) untuk berubah, penerimaan lingkungan sosial, dan kesiapan istri secara personal. Sejumlah penelitian terdahulu memperingatkan tentang efek perceraian terhadap kesejahteraan psikologis individu yang bercerai di masa yang akan datang (Feldman, 2018), serta kondisi psikologis anak ( Siegelman & Rider, 2018;Garriga & Pennoni, 2020).…”
Section: Diskusiunclassified